Balancing average capacitor voltages in neutral-point-clamped converters using band-limited three-level modulation - Beniwal, Neha (2020)
In this paper, a band-limited three-level modulation scheme is presented which aims to balance the average capacitor voltages in neutral-point-clamped converters under all load operating conditions. Compared to previous three-level modulation schemes, the proposed scheme provides a trade-off between voltage balancing performance and switching losses. Consequently, helping in optimizing the system’s footprint and its operating cost. A variable current band is calculated in order to provide the necessary control action for balancing the average (as opposed to instantaneous) capacitor voltages. The proposed modulation scheme is tested under both linear and nonlinear loads. A comparison is also performed between the proposed band-limited three-level modulation and other modulation schemes presented in the literature.